Pathogenetic justification of sacubitril / valsartan use in respiratory-cardial comorbidity - T. V. Ashcheulova; K. M. Kompaniiets; N. M. Herasymchuk; I. V. Sytina (Zaporozhye State Medical University, 2023)
Among the comorbid conditions that significantly worsen quality of life and life expectancy are the chronic obstructive pulmonary disease and heart failure. Difficulties of drug therapy are the mutually exclusive approaches in the treatment of chronic obstructive pulmonary disease and concomitant cardiovascular pathology. Aim of this study was to provide scientific evidence of the possible use of the combined drug LCZ696 (angiotensin receptor neprilysin inhibitor, ARNI), which contains neprilysin inhibitor sacubitril (AHU377) and angiotensin II blocker valsartan, in patients with congestive heart failure. The article presents a review of the literature. It was demonstrated that the cause of mortality in patients with chronic obstructive pulmonary disease could be both changes in the respiratory system and complications in the cardiovascular system. It has been shown that progressive chronic obstructive pulmonary disease leads to the formation of pulmonary hypertension, right ventricular hypertrophy, decrease in its systolic function, subsequent dilatation of the right ventricle, and development of right ventricular heart failure, which is one of the most serious and difficult tests in the treatment process. The further development of such a combined pathology is left ventricular heart failure. The role of the system of natriuretic peptides, namely brain natriuretic peptide, brain natriuretic propeptide, C-type natriuretic peptide, and N-terminal precursor of C-type natriuretic peptide, as markers of chronic obstructive pulmonary disease and heart failure has been discussed. Natriuretic peptide is currently a recognized marker of heart failure, the high value of which is achieved for determining the prognosis and stratification of the risk of heart failure. Natriuretic peptide acts as a vasodilator, provides antiproliferative activity through the G-dependent protein kinase pathway and promotes bronchodilation, causing the release of acetylcholine from bronchial epithelial cells. Conclusions. All these properties suggest that natriuretic peptides may be a potential treatment in patients with cardiac complications and chronic obstructive pulmonary disease. The best way to prolong life of natriuretic peptide is to inhibit degradation of the natriuretic peptide with the neprilysin inhibitor sacubitril.